Cadmium as an endocrine disruptor: Correlation with anterior pituitary redox and circadian clock mechanisms and prevention by melatonin - Jiménez Ortega, Vanesa (2012)
To examine the effect of a low dose of cadmium (Cd) as an endocrine disruptor, male Wistar rats received CdCl2 (5 ppm Cd) in drinking water or drinking water alone. After 1 month, the rats were euthanized at one of six time intervals around the clock and the 24-h pattern of adenohypophysial prolactin (PRL) synthesis and release, lipid peroxidation, and redox enzyme and metallothionein (MT) gene expression was examined. Cd suppressed 24-h rhythmicity in expression of the PRL gene and in circulating PRL by increasing them at early photophase only, in correlation with an augmented pituitary lipid peroxidation and redox enzyme expression. CdCl2 treatment effectively disrupted the 24-h variation in expression of every pituitary parameter tested except for MT-3. In a second experiment the effect of melatonin (3 μg/ml in drinking water) was assessed at early photophase, the time of maximal endocrine-disrupting effect of Cd. Melatonin treatment blunted the effect of Cd on PRL synthesis and release, decreased Cd-induced lipid peroxidation, and counteracted the effect of Cd on expression of most redox enzymes. A third experiment was performed to examine whether melatonin could counteract Cd-induced changes in the 24-h pattern of pituitary circadian clock gene expression and plasma PRL, luteinizing hormone (LH), thyrotropin (TSH), and corticosterone levels. Rats receiving CdCl2 exhibited a suppressed daily rhythm of Clock expression and a significant disruption in daily rhythms of pituitary Bmal1, Per1, Per2, Cry1, and Cry2. The coadministration of melatonin restored rhythmicity in Clock and Bmal1 expression but shifted the maxima in pituitary Per1, Cry1, and Cry2 expression to the scotophase. Melatonin also counteracted the effect of Cd on 24-h rhythmicity of circulating PRL, LH, TSH, and corticosterone. The results highlight the occurrence of a significant endocrine disruptor effect of a low dose of Cd. Generally melatonin counteracted the effects of Cd and ameliorated partially the circadian disruption caused by the pollutant.